FR4-Only Microstrip Reflectarray Antennas for 5.8 GHz Dual-Polarized Wireless Bridges - Honarbakhsh, Babak (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Low-cost antennas are suggested for 5.8 GHz narrow-band, low-power and dual-polarized wireless bridges based on pure microstrip flat reflectarrays. A single layer of the cheapFR4 epoxy is exploited as the substrate for both of the feed and reflector. Detailed design procedure for the feed is reported. Three different elements are used for designing the reflector including rectangular dipole, unbalanced cross and square patch. Using method of moments, performance of the designs is compared from various aspects, including reflector diameter, computational cost, gain, half-power beam-width and polarization purity.